Audit Sistem Informasi Keuangan Kas Perumahan Pondok Kelapa Menggunakan Framework COBIT 2019 - Vita Rahayu; Rena Amalia Hasibuan; Alfred Januardi (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2025)
For good cash management for company income, determining responsibility is the main goal. This ensures that there is sufficient cash available, not too much, but not too little, to compromise the company's liquidity. For the purpose of assessing IT governance, Pondok Kelapa Housing was chosen due to the fact that technology can help manage village finances. COBIT 2019 is a standard that can be used to measure the use of information technology. Therefore, an audit was carried out on the Pondok Kelapa Housing Cash financial information system application (SISKASPokel) to find out whether the system application was effective, efficient and manageable, and whether the application met end-user needs. In COBIT 2019, the two main topics are governance and management. DSS (Deliver, Service, and Support) is a process sub domain owned by management. The objective capability level of the process shows that the activity has been running but has not been completed well. The objective capabilities of DSS02 and DSS03 are at level 2 with an achievement score of 81.53%. At level 3, DSS02 and DSS03 capabilities are at level 3. With GAP recommendations, it is hoped that important company data or information can be improved.